CD169 Expression in Lymph Nodes is Associated with Increased Infiltration of CD8+ T Cells in Tumors: A Systematic Review and Meta-Analysis - Yong Wang; Xiao-Ting Wu; Jing Chen (Journal of Immunology Research)
The density of CD169+ macrophages has been reported to positively correlate with the number of CD8+ T cells, although this remains controversial. To better understand this topic, we conducted a meta-analysis. We searched the PubMed, Medline, and Web of Science databases for studies that were published before May 2022 and performed a meta-analysis of the incidence of low and high CD169 expression in groups based on CD8 expression using the random-effects model. A total of 10 studies were included in the meta-analysis. The incidence of high CD169 expression in lymph nodes was significantly lower than that of low CD169 expression in the low CD8 expression group (odds ratio (OR): 0.76, 95% confidence interval (CI): 0.6, 0.96); however, the incidence of high CD169 expression in lymph nodes was higher than that of low CD169 expression in the high CD8 expression group (OR: 1.50, 95% CI: 1.08, 2.07). We also found that the expression of CD169 in tumors was lower than that in nontumor tissues (standardized mean difference: −5.29, 95% CI: −7.47, −3.11). The overall survival and hazard ratio of patients with high and low CD169 expression was 0.45 (95% CI: 0.37, 0.55). This analysis showed that high CD169 expression was associated with a high CD8 expression, and low CD169 expression was associated with low CD8 expression. The risk of death was 55% lower for patients with high CD169 expression, and high CD169 expression may be associated with favorable survival outcomes in cancer patients. However, the number and heterogeneity of the studies should be taken into consideration when evaluating the analysis. High-quality randomized controlled trials on the association between CD169 and CD8 expression are needed to verify these effects.